Luther's necessitarian argument in De servo arbitrio - Kraal, Anders (Religious studies, 2016)
In De servo arbitrio (1525) Luther famously argues that the divine attributes of will, power, foreknowledge, and immutability are incompatible with (human) free will, and hence that free will is a name with no reality'. I survey some earlier explications of Luther's argument in the literature, and reject them as exegetically unsound. I then go on to propose a new explication. On the proposed explication, Luther's argument turns out to be theologically cogent, provided that we follow Luther in understanding the relevant divine attributes in accordance with Augustinian theology.